(untitled) (Al-Academy, 2018)
The earthly music has a clear influence on the religious music in the musical culture to read and recite the Holy Quran in the city of Baghdad. This research deals with this subject in an attempt to reveal the influence of the Iraqi maqam in the recitation of Hafiz Khalil Ismail. The methodological framework of the research included the problem of research and its importance as it is useful to the Iraqi schools concerned with the recitation of the Holy Quran in Iraq. The theoretical framework included three sections that serve the literature of its subject: the first is (Iraqi maqam), the second is (the recitation of the Holy Quran) and the third is (the biography of Hafez Khalil Ismail). The most important procedures were determining the research community, sample and methodology. The researcher adopted the analytical descriptive approach in dealing with the samples, and through the analysis of the samples, the researcher reached the most important results and conclusions. The most important result is the existence of a great influence of the Iraqi maqam in the recitation of Hafez Khalil Ismail that all his recitation is from the melodies of the Iraqi maqam. The research ends with the footnotes and the sources, and the summary of the research in English.